Evaluasi Kepuasan Konsumen Vertical Garden di PT Archileaf - alfi haryo; Armaeni Humaerah (Program Studi Agribisnis UIN Syarif Hidayatullah Jakarta, 2022)
Ornamental plants indoors (indoor plants) and outdoors (outdoor plants) can encourage the urban farming movement. As a potential business, the development of ornamental plant business at PT. Archileaf can be run and on the one hand looks quite profitable financially. However, the company must evaluate the services offered. This research was conducted with the aim of: Identifying the level of customer satisfaction in vertical garden making services at PT. Archileaf. Knowing the suitability between consumer expectations and service performance at PT. Archileaf. Knowing the attributes that need to be improved in improving service quality at PT. Archileaf. The data used in this study are: Primary data obtained through interviews with PT. Archileaf, the results of filling out the questionnaire directly from the respondents, and the results of observations. Secondary data obtained from literature review taken through literature from books, websites, scientific journals, theses and other writings related to this research. The method used in this research is the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) which are processed with Microsoft Excel 2016 software tools and SPSS version 20 for Windows. The results of this study obtained that the analysis of the level of consumer satisfaction produces a CSI value of 74.79%, which means that consumers are satisfied, while the opportunity for dissatisfaction is 25.21%. The level of conformity between the level of performance and the level of expectation is 87.59% and the chance of discrepancy is 12.41%. There are 5 priority attributes for improvement (responding to consumers, timely maintenance, plant warranty quality, company attitude and discount information) and attributes that must be maintained by PT. Archileaf has 15 attributes. Keywords: Vertical Garden, Expectations, Performance, Satisfaction, Consumers Abstrak:Tanaman hias di dalam ruangan (indoor plant) dan di luar ruangan (outdoor plant) dapat mendorong gerakan urban farming. Sebagai bisnis yang potensial, pengembangan bisnis tanaman hias di PT. Archileaf dapat dijalankan dan di satu sisi terlihat cukup menguntungkan secara finansial. Namun, perusahaan harus mengevaluasi layanan yang ditawarkan. Penelitian ini dilakukan dengan tujuan untuk: Mengidentifikasi tingkat kepuasan pelanggan pada jasa pembuatan taman vertikal di PT. Archileaf. Mengetahui kesesuaian antara harapan konsumen dengan kinerja pelayanan pada PT. Archileaf. Mengetahui atribut-atribut yang perlu ditingkatkan dalam meningkatkan kualitas pelayanan pada PT. Archileaf. Data yang digunakan dalam penelitian ini adalah: Data primer diperoleh melalui wawancara dengan PT. Archileaf, hasil pengisian kuesioner langsung dari responden, dan hasil observasi. Data sekunder diperoleh dari studi pustaka yang diambil melalui literatur dari buku-buku, website, jurnal ilmiah, tesis dan tulisan-tulisan lain yang berhubungan dengan penelitian ini. Metode yang digunakan dalam penelitian ini adalah Customer Satisfaction Index (CSI) dan Importance Performance Analysis (IPA) yang diolah dengan perangkat lunak Microsoft Excel 2016 dan SPSS versi 20 for Windows. Hasil penelitian ini diperoleh bahwa analisis tingkat kepuasan konsumen menghasilkan nilai CSI sebesar 74,79% yang berarti konsumen puas, sedangkan peluang ketidakpuasan sebesar 25,21%. Tingkat kesesuaian antara tingkat kinerja dengan tingkat harapan sebesar 87,59% dan peluang terjadinya selisih sebesar 12,41%. Ada 5 atribut prioritas untuk perbaikan (menanggapi konsumen, perawatan tepat waktu, kualitas garansi pabrik, sikap perusahaan dan informasi diskon) dan atribut yang harus dipertahankan oleh PT. Archileaf memiliki 15 atribut. Kata Kunci: Taman Vertikal, Harapan, Kinerja, Kepuasan, Konsumen